Creation of the first UXO detection test site in Slovakia at the Rohožník military training range - PAŠTEKA, Roman; KARCOL, Roland; KUŠNIRÁK, David; NOGOVÁ, Ema; ANDRÁSSY, Erik (Contributions to Geophysics and Geodesy, 2023)
In the development of geophysical methods for unexploded ordnance detection, a very important role is played by UXO test sites, where known ordnance and other explosive/nonexplosive items are buried in the ground at defined positions. At such sites, various detection methods can be compared, developed and tested. Based on a cooperation between the Department of Applied Geophysics (Comenius University), Institute of Forensic Science (Slovak Ministry of Interior) and Rohožník military training range a project was performed, which was focused on the creation of the first UXO detection test site in Slovakia. It was restricted to one type of ordnance – inert tank projectiles with diameter of 100 mm. These were buried in the ground at different depths and with different orientations. Data acquisition mapping the test site was performed from the ground surface, using total field intensity magnetometers, vertical difference magnetometers and ground penetrating radar (GPR). Data acquired from all methods were processed, interpreted and archived for future reference. Most of the items were readily detected by each of the detection sensors used but the deepest items at the least favourable orientation exceeded the detection limit of the magnetometers trialled with total field performing better than the vertical gradiometers. For the application of GPR, this site was found to have favourable soil conductivity conditions permitting even the deepest items to be detected when favourably oriented. Vertical orientation presenting the smallest reflective cross-section was least favourable with some shallow items escaping detection. The most accurate depth estimations for detectable items were obtained from GPR data presented as 2D non-migrated vertical sections. Geophysical data sets acquired at seeded test sites such as the one now established at the Rohožník military training range can provide important base-line data for comparison from which development of new detection and data interpretation technologies can be evaluated.